Gênero e trabalho no setor público: um estudo de caso do segmento técnico-administrativo da UFU - Marques, Alinne Gomes (2016)
This work analyses the working relationships in the technical and administrative sector of the Federal University of Uberlandia (UFU), considering the world of work as one of the many dimensions in which social relationships concerning gender are structured. This work aims to gather information that may contribute to discussions related to the promotion of equality between men and women in the workplace. This research profiles the technical and administrative sector of UFU, investigating the career development of men and women, and the development of actions that promote gender equality within the university. This research is a study case in which quantitative and qualitative evidences resulting from institutional indicators were gathered. Data were collected of a sample from the population studied. The assessment of the data is anchored in the analytical approaches that consider gender as an organizing principle of society and that seek to understand the inequalities established from it, in its dynamic reconfiguration, as a product of social practices and relations. The results revealed the dynamic structuring of inequalities in working relationships in the sector analyzed, contributing to the deconstruction of the presumed notion of gender equality in the public sector.